Profil Critical Thinking Appraisal For Environmental Science (Cta-Es) Siswa Kelas XI IPA SMA Negeri Kota Pontianak - Sri Citra Mulyani; Afandi; Titin (Jurnal Ilmiah Edukatif, 2023)
This research aims to determine the profile of critical thinking appraisal for environmental science (CTA-ES) of class indicator. The instrument used was the critical thinking appraisal for environmental science (CTA-ES) test questions, totaling 39 questions consisting of 5 critical thinking indicators according to Watson and Glaser. The method used in this research is a quantitative method with descriptive research type. The data collection technique is carried out by distributing test questions to a predetermined sample. The data source in this research is class Data analysis in this research was carried out by examining and calculating the scores of answers chosen by students, determining criteria and drawing conclusions. The results of this research show that the critical thinking appraisal for environmental science (CTA-ES) profile of students in class XI Science at SMA Negeri Pontianak City has an average score of 57.43 in the less critical category. The description of the critical thinking appraisal for environmental science (CTA-ES) of class The assumption recognition indicator is in the critical category (72.22). The indicator for making deductions is in the less critical category (59.01). The indicator makes the interpretation in the less critical category (54.11). The indicator for analyzing arguments is in the critical category (70.12).